Combining polymers and additives for sustainable asphalt binder performance - Aydin, Hakan; Yalcin, Erkut; Yilmaz, Mehmet; Ozdemir, Ahmet Munir; Alatas, Taner (Elsevier, 2025)
The viscoelastic and thermoplastic nature of bituminous materials makes them highly sensitive to factors such as temperature changes, extreme and repeated loading, and UV radiation. To prevent this sensitivity from causing significant structural problems, bitumen must exhibit behavior characterized by desirable properties. The most common method to achieve this is through polymer modification. To date, a wide variety of polymers have been used for bitumen modification, and recent research has increasingly focused on using different polymers together. In this study, 611 elastomer, crumb rubber (CR), and melastol-crumb rubber (MCR) were used both individually and in combination as modifiers. Their physical, rheological, and mechanistic behaviors were thoroughly investigated. The findings indicate that binders modified with 611 and MCR exhibited superior rheological properties, including increased stiffness, elasticity, and resistance to permanent deformation when compared to those modified with SBS and CR. The best performance was obtained from the binder containing 3.5 % 611 additive. It improved the high temperature performance of the pure binders. The findings also highlight the sustainability potential of this approach, since the incorporation of recycled melastol crumb rubber (MCR) reduces waste and the required dosage of virgin elastomer, thereby supporting environmentally and economically sustainable pavement practices. Future research should emphasize field trials and long-term performance evaluations to validate these laboratory findings.
Keywords: Bitumen; SBS; Crumb rubber; Modification; Rheology